Cross-Cultural Advertising in Southeast Asia: Market Trends, Digital Engagement, and Cultural Adaptation - Saipul (Communica : Journal of Communication, 2024)
This study aims to analyze cross-cultural advertising in Southeast Asia (SEA) between 2019 and 2024, with particular attention to market growth, digital engagement, and cultural adaptation strategies that influence advertising effectiveness. A mixed qualitative-quantitative approach was employed, relying on secondary data from Mordor Intelligence, EMARKETER, and Campaign Asia. Theoretical frameworks from Hofstede’s cultural dimensions, Hall’s high/low context theory, and postcolonial perspectives were applied to interpret advertising practices. Findings indicate that campaigns integrating local languages, regional influencers, and visual storytelling outperform standardized global content. Mobile-first strategies aligned with cultural values increase engagement, while high-context communication enhances message retention. Personalized mobile content and culturally embedded apps strengthen consumer trust and loyalty. The study concludes that cultural adaptation is essential for effective advertising in SEA. Inclusive and culturally attuned strategies foster stronger brand loyalty and higher conversion rates. The insights provide practical guidance for marketers operating in the region’s competitive and diverse digital markets.